A Novel and Disposable Enzyme-Labeled Amperometric Immunosensor Based on MWCNT Fibers for Listeria monocytogenes Detection. (13th June 2016) - Lu, Ying; Liu, Yongling; Zhao, Yong; Li, Wenjiao; Qiu, Longbing; Li, Li
Abstract : A sensitive and specific immunosensor was developed by immobilizing HRP-labeled antibody against Listeria monocytogenes onto the surface of the novel multiwalled carbon nanotube fibers. Firstly, the influence of immunoelectrode modification methods (chemical and physical method) on detection sensitivity and stability was studied. Next, immunosensor was developed, optimized, and applied for the detection of L. monocytogenes . The morphology was characterized by scanning electron microscopy (SEM), and electrochemical behaviors were by cyclic voltammetry. SEM image, relative response (%), and current data showed chemical modification for immunoelectrode was helpful to capture more target bacteria and obtain more stable current response, resulting in improving the detection sensitivity. The linear relationship between L. monocytogenes concentration andΔ I p c was from 10 2 to 10 5 cfu/mL (R 2 = 0.993 ), and LOD was1.07 × 10 2 cfu/mL. L. monocytogenes in mixed bacteria (1.51 × 10 3 cfu/mL) of milk sample (S/N > 14) were detected by developed immunosensor, showing good specificity. Good storage stability and reproducibility (RSD < 6.5%) also showed the potential application of immunosensor for the rapid detection of L. monocytogenes .